2008
DOI: 10.18267/j.pep.328
|View full text |Cite
|
Sign up to set email alerts
|

Economic value added (eva) as a performance measurement for glcs vs non-glcs: evidence from bursa malaysia

Abstract: Ab stract:EVA is a use ful tool for as sess ing com pany per for mance. It com bines fac tors, such as econ omy, ac count ing and mar ket in for ma tion in its as sess ment. This study em ployed EVA in an at tempt to com pare the com pa nies' per for mances of GLCs (gov ern ment-linked com pa nies) and non-GLCs. Based on a 4-year pooled panel data of 37 GLCs and 208 non-GLCs, the re sults show that com pa nies with gov ern ment as their stake holders tend to ex hibit lower EVA scores than the com pa nies with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…The reason behind is firm's expansion in the size could incur a greater increment in capital cost proportion as compared to the earnings generated. This outcome is consistent Issham et al (2008) as they also concluded that large size and government linked firms are more likely to have lower EVAs. Same result also has been found by Hudaib and Haniffa (2006).…”
Section: Multiple Regression Analysissupporting
confidence: 81%
“…The reason behind is firm's expansion in the size could incur a greater increment in capital cost proportion as compared to the earnings generated. This outcome is consistent Issham et al (2008) as they also concluded that large size and government linked firms are more likely to have lower EVAs. Same result also has been found by Hudaib and Haniffa (2006).…”
Section: Multiple Regression Analysissupporting
confidence: 81%
“…In this context, Machuga et al (2002) experienced mixed results concentrating on the relationship that exists between EVA and stock returns. Such type of findings was supported by Chattopadhyay and Das (2006), Issham et al (2007); and Nappi-Choulet and Missonier-Piera (2007). Banerjee and Jain (1999) conducted an empirical research in this field.…”
Section: Introductionmentioning
confidence: 61%
“…Several authors like Young (1997); Issham et al (2008) [36], and Silverman (2010) [37] used the model of EVA developed by Stern and Stewart to inspect the creation of value to shareholders. However, there were some variation in the explanation and calculations by different au-thors from which four of them are mentioned in this paper.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Value is created only if the return generated by using the net assets surpasses the cost of capital. Issham et al (2008), defined EVA as the dollar amount of charges for capital (both debt and equity) are subtracted from the dollar amount of net operating after tax (NOPAT) net operating after tax, calculated figure is multiplied with the percentage of weighted average coat capital. Issham et al further state that EVA is an estimate of the amount by which earning exceeds or fall short of the rate of return shareholders could get by investing in other securities of comparable risk and includes a charge against profit for the cost of all capital a firm employs.…”
Section: Empirical Evidencementioning
confidence: 99%